1995
DOI: 10.1111/j.1476-5381.1995.tb17236.x
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of different organic nitrates to elicit NO formation in rabbit vascular tissues and organs in vivo

Abstract: 1 In the present study we assessed the formation of nitric oxide (NO) from classical and thiolcontaining organic nitrates in vascular tissues and organs of anaesthetized rabbits, and established a relationship between the relaxant response elicited by nitroglycerin (NTG) and NO formation in the rabbit isolated aorta. Furthermore, the effect of isolated cytochrome P450 on NO formation from organic nitrates was investigated. the animals were killed, blood vessels and organs were removed, and subsequently analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 27 publications
3
31
1
Order By: Relevance
“…A possible explanation for the differential actions is that sGC activation by NTG depends on the biotransformation of NTG, which has been reported to be higher on the venous side. 8 Furthermore, cGMP-independent actions of NO may account for the differences. Importantly, in addition to concerns regarding mitochondrial toxicity associated with nitrate bioactivation, 3 there is controversy about some poten- tially adverse consequences of cGMP-independent actions of NO such as peroxynitrite generation, nitrosation, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the differential actions is that sGC activation by NTG depends on the biotransformation of NTG, which has been reported to be higher on the venous side. 8 Furthermore, cGMP-independent actions of NO may account for the differences. Importantly, in addition to concerns regarding mitochondrial toxicity associated with nitrate bioactivation, 3 there is controversy about some poten- tially adverse consequences of cGMP-independent actions of NO such as peroxynitrite generation, nitrosation, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Umbilical cords obtained from the Department of Gynaecology (Faculty of Medicine of Valencia) were cut into rings (5 mm) and placed in Krebs solution ([in ϫ10 Ϫ3 mol/L] NaCl 118, KCl 4.75, CaCl 2 1.9, MgSO 4 1.2, KH 2 PO 4 1.2, NaHCO 3 25, and glucose 10.1). Human umbilical vein cells (HUVECs) and human umbilical arterial endothelial cells (HUAECs) were cultured in medium 199 (Cambrex, Walkersville, Md) as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…have generally been attributed to its bioconversion into the relaxant agent nitric oxide (NO), which acts on the enzyme soluble guanylate cyclase (sGC). [1][2][3] However, most studies that support the existence of such a pathway have demonstrated increases of NO only when GTN concentrations considerably exceeded the plasma levels reached during clinical dosing. 4 Moreover, the involvement of other NO-related species in the actions of GTN when used at clinically relevant concentrations is also under debate.…”
mentioning
confidence: 99%
“…Although the details of GTN metabolism are not fully understood, possible pathways yielding 1,2-glyceryl dinitrate and NO 2 − have been suggested 3) and those yielding 1,2-glyceryl dinitrate and NO, part of the latter may be the source of NO 2 − , have also been reported. 4) Increases in NO and NO 2 − by ISDN have been reported not only in vitro, 7,15,25,29,30) but also in vivo, 29,30) although the possible metabolic pathways, including whether NO 2 − is a direct or indirect product, are not fully elucidated. Nevertheless, the dose-dependent increase in plasma NO 2 − with concomitant decrease in blood pressure by ISDN is in good agreement with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The weak inhibitory effect of cyanamide on GTN-induced hypotension with concurrent small increase in plasma NO 2 − indicate that, in whole animal, cyanamide-insensitive bioactivation mechanism(s) could be largely operative in organs other than vascular smooth muscle. Indeed, it is reported that the formation of NO by GTN is quite larger in liver, lung and kidney than vascular tissues in rabbits 31,30) and that high doses of GTN are metabolized by several other enzymes (low affinity pathway), including glutathione-S-transferases, xanthine oxidoreductase, and cytochrome P450. 5) These possible mechanisms might release at least small amounts of NO 2 − or NO into the plasma where the latter is easily affected by oxidation to yield NO 2 − .…”
Section: Discussionmentioning
confidence: 99%